Transmission Routes of COVID-19: a Review of the Evidence - Sharif, Amin sadat (Journal of Pediatric Nephrology, 2020)
Since early December 2019, the Coronavirus Disease 19 (COVID-19) infection has been prevalent in China and in the short term, the virus has spread to other countries. Due to the short duration of the virus pandemic, few studies have been reported on transmission routes. Identifying ways of transmitting the disease will be very effective in preventing its spread. We reviewed the methods of transmission of COVID-19 including droplets, contact, airborne, vertical transmission to the fetus of infected mothers and fecal-oral by using data of published articles or official websites up to Apr 19, 2020. The most important routes of transmission of COVID-19 were droplets and contacts. The presence of the virus in the stool, even after a negative nasopharyngeal swab, was another major cause of shedding of infection. No maternal to fetus vertical transmission was seen. Infant is at risk after birth only through droplets during breastfeeding. Based on limited data, droplets, contact, airborne and fecal transmissions are important ways of transmitting the disease and there is no evidence for intrauterine transmission of COVID-19 from infected pregnant women to their fetuses. Keywords: Corona virus; COVID-19; Droplet; Contact, Airborne; Vertical transmission; Fecal.